EJBM 2019
DOI: 10.7176/ejbm/11-19-01
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Assessment of Financial Distress in Textile Sector of Pakistan (2012-2018)

Abstract: As business expand in modern global economy, cutthroat competition also becomes a reality. It becomes more important for businesses not only to diversify but also to break through with their respective products on different markets through cost cutting techniques and technologies. For survival and carrying on business activities, an organization should have to manage their finances on priority matters that need utmost care and attention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…The increase in the TATO ratio shows that the more efficient the company is in managing its assets so that it is increasingly protected from financial difficulties. This is supported by the results of research by Santosa et al (2020), Ramadhan (2021), Khan (2019) which found that activities have a significant negative effect on financial distress. H4: activities have a negative influence on financial distress.…”
Section: The Effect Of Activities On Financial Distressmentioning
confidence: 53%
See 1 more Smart Citation
“…The increase in the TATO ratio shows that the more efficient the company is in managing its assets so that it is increasingly protected from financial difficulties. This is supported by the results of research by Santosa et al (2020), Ramadhan (2021), Khan (2019) which found that activities have a significant negative effect on financial distress. H4: activities have a negative influence on financial distress.…”
Section: The Effect Of Activities On Financial Distressmentioning
confidence: 53%
“…The more ROA increases, the better the company's condition so that it is increasingly protected from financial distress. The results of research by Nurhamidah (2021), Handayani (2020), Rudiyanto (2021), Mahaningrum (2020), Ramadhan (2021), Dwiantari (2021), Isayas (2021), Khan (2019), Kamaluddin (2019), Balasubramanian (2019) and Waqas (2018) found that profitability has a significant negative effect on financial distress. H1: profitability negatively affects Financial Distress.…”
Section: Research Hipotesis the Effect Of Profitability On Financial ...mentioning
confidence: 99%